(untitled) (Alberta Journal of Educational Research, 2006)
Based on theories of emotional intelligence, adult education, psychology of reading, and emotions and literature, this study was designed to develop and validate the Affective Response to Literature Survey (ARLS), a psychological instrument used to measure an emotional response to literature. Initially, 27 items were generated by a review of research relevant to emotional intelligence and emotional effects of literature. A panel of 10 experts rated 27 proposed items. After applying the content validity ratio to the expert’s ratings, 18 items were retained. The instrument was then administered to 165 individuals to assess psychometric properties. The ARLS demonstrated high internal consistency (Cronbach’s alpha=.90) and test-retest reliability (r=.90, p < .001). Factor analysis extracted four factors: (a) Reflective Synthesis, (b) Acting with Volition, (c) Processing, and (d) Empathetic Responding. The four factors have important implications for conducting research sensitive to literature, emotional intelligence, and transformational learning.